Structural studies on hepatitis C virus (HCV) NS5A and its molecular interaction with CypA - Lee, Jia Jun (2015)
Hepatitis C virus infection is a worldwide issue and its NS5A protein interacts with host Cyclophilin A to play a crucial role in viral replication. To date, there is limited structural information for the intrinsically disordered NS5A protein. Here, low-resolution models of NS5A and NS5A-CypA from small-angle X-ray scattering data were presented. The models suggest NS5A adopt an extended conformation and binding to CypA may induce NS5A-D1 dimerisation, similar to published data. NS5A-D2 and NS5A-D3 may bind CypA in random coil conformation. Residue P314 of NS5A-D2 is necessary and sufficient for this interaction. The CypA recognition site of NS5A-D2 binds to a region very close to CypA R55 residue, which is responsible for stabilization of the transition state for PPIase activity. A peptide of NS5A-D2 containing the CypA recognition site is able to perturb the conformation of CypA substrate binding cavity and inhibits HCV replication in HCV subgenomic replicon system.